Redox dye–mediated fluorescence energy transfer of carbon nanotube–based nanosensors - Shoichi Nishitani; Kevin Ao; Amad Jalil; Octavio I. Arias-Soto; Ava Moudi; Feiyang Chen; Ankita Biyani; Padma N. Muppirala; Markita P. Landry (Proceedings of the National Academy of Sciences, 2025)
Single-walled carbon nanotubes (SWCNTs) exhibit nonphotobleaching, near-infrared (NIR) fluorescence suitable for bioimaging applications. In particular, SWCNT fluorescence quenching induced by biopolymer dispersants facilitates flexible design of molecular nanosensors, yet challenges remain in analyte selectivity and lack of rational design strategies. A sought-after alternative to haphazard molecular modulation of SWCNT-based fluorescence is to couple the movement of a quencher to the SWCNT surface, enabling fluorescence energy transfer to modulate molecular recognition with high selectivity. This study presents the rational design of SWCNT-based nanosensors with fluorescence energy transfer, leveraging the unique properties of methylene blue (MB) proximity–mediated fluorescence quenching. MB-SWCNT-based nanosensors exhibit 1- stability in redox environments and 2- analyte-specific displacement-driven fluorescence modulation. By designing hybridization-induced displacement of MB-conjugated ssDNA from the SWCNT surface, we calculate that SWCNT fluorescence modulation can occur within a 6.8 nm fluorescence resonance energy transfer distance from the SWCNT surface and develop a robust and versatile platform to synthesize oligonucleotide nanosensors with tunable Δ F / F 0 of up to 150%. Building upon this strategy, we developed four distinct nanosensors capable of selectively detecting tobacco mosaic virus (TMV) viral RNA fragments, which successfully differentiated TMV-infected plants from mock controls. Finally, we demonstrate the potential expansion of our design to target a wider scope of biomolecules using the biotin-avidin system as a model. Taken together, our study presents a generalizable platform that enables rational engineering of SWCNT NIR fluorescence intensity through MB distance-dependent fluorescence energy transfer, overcoming the intrinsic selectivity challenges of current SWCNT nanosensors.